Menggugat Larangan Wanita Haid Berdiam Dalam Masjid (Perbandingan Pandangan Imam al-Syafi’i dan Imam Ahmad) - Mulyana Mulyana; Roswati Nurdin; H Rajab (Muqaranah, 2022)
This is research on the prohibition of Menstruating Women Staying in the Mosque according to Imam al-Shafi'i and Imam Ahmad bin Hanbal. In Indonesia, the presence of menstruating women in mosques is still considered prohibited, because the Indonesian Muslim community generally adheres to the Shafi'i school of thought. However, this opinion began to be sued because it was considered to discriminate against women because it prohibited them from being involved in activities at the mosque. On the other hand, there is the view of Imam Ahmad who does not question the presence of menstruating women in the mosque. This study aims to compare the opinions of the two Imams to find which one is more appropriate to the times and not discriminatory. This research is library research that relies on data sources from written data, both in the form of books and journal articles. This study uses a comparative qualitative approach. The results of the study show that according to Imam Ahmad, there is no strong argument that prohibits menstruating women from entering and staying at the mosque. The hadith which prohibits menstruating women from entering and staying in the mosque is a daif hadith because there are majhul narrators. Meanwhile, Imam al-Shafii took an attitude of ihtiyath by continuing to practice the hadiths above, so that only menstruating women were allowed to pass inside the mosque, without stopping and remaining silent.